Clinical and laboratory diagnosis of autoimmune factor V inhibitors: A single institutional experience. Issue 171 (November 2018) - Sridharan, Meera; Fylling, Kara A.; Ashrani, Aneel A.; Chen, Dong; Marshall, Ariela L.; Hook, C. Christopher; Cardel, Laynalee K.; Nichols, William L.; Pruthi, Rajiv K.
Abstract: Background: Coagulation factor V inhibitors (FV-i) may occur in patients with congenital FV deficiency or previously hemostatically normal patients (autoimmune (AI)-FV-i). Most of the published literature is confined to case reports. Objective: Describe clinical and laboratory features of AI-FV-i identified through the Special Coagulation Laboratory at Mayo Clinic, Rochester, Minnesota. Methods: In this retrospective study individuals with FV-i screens performed from January 1999 to February 2017 were identified through the special coagulation laboratory database. Clinical presentation, management, and outcomes were collected for our institutional patients while detailed laboratory data was collected for all tested patients. Results: Of patients with FV-i managed at our institution, 2/8 (25%) patients experienced no bleeding. There was no correlation between inhibitor titers and/or FV activity (FV:C) levels and clinical bleeding. Hemostatic management included fresh frozen plasma, platelet transfusion, activated prothrombin complex concentrates, and recombinant factor VIIa. Only 2 patients received immunomodulatory treatment. FV-i mixing studies with normal pooled plasma ( n  = 26) demonstrated inhibition on immediate mix but progressive inhibition after 1 h of incubation could not be demonstrated. 71% of platelet neutralization procedures were falsely positive while 59% of DRVVT assays were indeterminate. Conclusion: FV-i demonstrates immediate inhibition on mixing studies; however our limited data does not support a time dependent inhibition. Our clinical cohort confirms the variable clinical phenotype for individuals with FV-i and supports the notion that management of FV-i should be guided by clinical symptoms and not FV:C or FV-i titer. Highlights: FV inhibitors demonstrate immediate inhibition on mixing studies. Individuals presenting with factor V inhibitors have a variable clinical phenotype. Clinical symptoms, not FV activity and inhibitor titer level, should guide management.